2015
DOI: 10.1016/j.jcin.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Single-Arm, Multicenter Trial of Ultrasound-Facilitated, Catheter-Directed, Low-Dose Fibrinolysis for Acute Massive and Submassive Pulmonary Embolism

Abstract: Ultrasound-facilitated, catheter-directed, low-dose fibrinolysis decreased RV dilation, reduced pulmonary hypertension, decreased anatomic thrombus burden, and minimized intracranial hemorrhage in patients with acute massive and submassive PE. (A Prospective, Single-arm, Multi-center Trial of EkoSonic® Endovascular System and Activase for Treatment of Acute Pulmonary Embolism (PE) [SEATTLE II]; NCT01513759).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
541
5
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 769 publications
(612 citation statements)
references
References 30 publications
24
541
5
17
Order By: Relevance
“…56,57 This combination offers an immediate hemodynamic effect, because the thrombus is ruptured mechanically, combined with a higher concentration of the fibrinolytic agent at the site, avoiding the systemic action of fibrinolytic therapy and reducing the risk of major bleeding. [58][59][60] The SEATTLE II study of 150 patients with massive or submassive PTE treated with 20 mg of rtPA demonstrated correction of RV dysfunction and of PH within 24 h in 30% of them, with no CNS bleeding, 61 and the ULTIMA study, with 59 patients, also observed rapid improvement in parameters of RV dilatation without major bleeding (just 3.6% minor bleeding). 62 The limitations of this technique are the need for a specialized team, the cost of the material, and as-yet scant scientific evidence, 21,40 which restricts its use to patients who will not respond well to systemic treatment.…”
Section: Patients With Submassive Pte (Moderate Risk)mentioning
confidence: 99%
“…56,57 This combination offers an immediate hemodynamic effect, because the thrombus is ruptured mechanically, combined with a higher concentration of the fibrinolytic agent at the site, avoiding the systemic action of fibrinolytic therapy and reducing the risk of major bleeding. [58][59][60] The SEATTLE II study of 150 patients with massive or submassive PTE treated with 20 mg of rtPA demonstrated correction of RV dysfunction and of PH within 24 h in 30% of them, with no CNS bleeding, 61 and the ULTIMA study, with 59 patients, also observed rapid improvement in parameters of RV dilatation without major bleeding (just 3.6% minor bleeding). 62 The limitations of this technique are the need for a specialized team, the cost of the material, and as-yet scant scientific evidence, 21,40 which restricts its use to patients who will not respond well to systemic treatment.…”
Section: Patients With Submassive Pte (Moderate Risk)mentioning
confidence: 99%
“…In one study, the use of femoral vein access was the only variable associated with major bleeding, compared to a brachial access (36). A short 7-10 Fr introducer sheath is usually adequate (9,10,27). Though, using a long sheath placed in the main PA can facilitate exchanges for catheter and thromboembolectomy devices.…”
Section: Access Sitementioning
confidence: 99%
“…The ULTIMA trial showed marked improvement in RV parameters without major complications in submassive PE (9). The Prospective, Single-arm, Multi-Center Trial of EkoSonic® Endovascular System and Activase for Treatment of Acute Pulmonary Embolism (SEATTLE II) trial, a single arm prospective study of 150 patients, showed a reduction in RVD and improvement in pulmonary hypertension in submassive and massive PE without any intracranial hemorrhage (10). The multicenter Pulmonary Embolism Response to Fragmentation, Embolectomy, and Catheter Thrombolysis (PERFECT) registry evaluated CDI for massive and submassive PE (11).…”
Section: Clinical Evidencementioning
confidence: 99%
“…After assessing the risks and benefits of the available options for both the mother and fetus, the team reached a consensus to proceed with CDT using an ultrasound-enhanced EKOS catheter ( Figure 2). The goal was to minimize risks to the mother and fetus and simultaneously optimize RV recovery (7,8).…”
Section: Casementioning
confidence: 99%